Design and characteristic analysis of fiber optic Fabry-Perot sensor for static ice strain monitoring - Mengxing HUANG; Yuhang LI; Guanjun WANG; Jianxun LIU; Lu YAN; Longjuan WANG (Tongxin xuebao)
Sea ice is one of the important natural disasters.A new method based on optical fiber Fabry-Perot sensor for ice strain measurement was proposed to meet the needs of ice strain monitoring.A high sensitivity optical fiber Fabry-Perot pressure sensor with thin-film structure was realized by means of pressure assisted arc discharge method,and the sensor was encapsulated by metal tube /PDMS /AB epoxy glue combination method.On this basis,the static internal strain characteristics of ice in the process of melting and freezing during -15℃～0℃ was studied.Experimental results show that this proposed thin-film fiber Fabry-Perot pressure sensor has good sensitivity characteristic in ice strain monitoring,it is believed of great value for the monitoring of remote distributed sea samples.